P04 Age- and gender-specific risk of death after first hospital admission for heart failure. (16th November 2010) - Vaartjes, I; Hoes, A W; Reitsma, J B; de Bruin, A; Grobbee, D E; Mosterd, A; Bots,
Abstract : Objective: Heart failure (HF) is an important public health problem. Detailed information on prognosis following hospital admission is crucial for cost-effectiveness analysis and determination of the burden of HF on the health care system. However, such data are scarce. Therefore, the objective of this study was to provide mortality risk following hospital admission stratified by age- and gender. Design: Hospital based follow-up study. Setting and Participants: A nationwide cohort of patients hospitalised for the first time for heart failure was identified through linkage of national registers in 1997 and 2000. The total population of the Netherlands in 1997 and 2000 was 15 567 107 (men 7 696 803, women 7 870 304) and 15 863 950 (men 7 846 317, women 8 017 633), respectively. Main Outcome Measure: The crude short-term (28 day), 1-year and long-term (5-year) mortality was computed by age and gender according to the actuarial life table method and expressed as percentages. The mortality rate in men was compared to mortality rate in women by calculating RR (with 95% CI). Results: 14 529 men, mean age 74±11 years and 14 524 women, mean age 78±11 years were identified. Mortality risk after admission for HF increased with age from 35–44 years to 75–84 years (men: 28-day mortality from 7.5% to 32.9%, 1-year mortality from 17.2% to 58.6% and 5-year mortality from 34.2% to 87.1%; and women: 28-day mortality from 6.9% to 27.2%, 1-year mortality from 14.9% to 49.9% and 5-year mortality from 27.6% to 84.1%). The risk of death was higher among man than women of the same age. Conclusions: There are clear age and gender differences in short- and long-term risk of death after first hospitalisation for heart failure. This information is helpful for clinicians, policymakers and service planners. Findings will also be useful for the development of models that evaluate cost-effectiveness and impact on outcomes of heart failure management programmes, and for predicting the future health care burden of heart failure.